Intercultural education for conscious entrepreneurship as an organizational resilience strategy. (Revista Electrónica Diálogos Educativos. REDE, 2026)
This study aimed to analyze how intercultural education, the Kaxan method, and a conscious entrepreneurship approach contribute to the emotional, organizational, and productive strengthening of entrepreneurs from informal economies, in contexts marked by structural inequality and limited access to employment opportunities. The research employed a qualitative approach, utilizing the systematization of experiences and narrative analysis of participants' life stories. Through in-depth interviews, reflective workshops, and guided introspective exercises, subjective, cultural, and organizational elements influencing the sustainability of these ventures were explored. The results show that the main barriers are not exclusively technical or financial, but rather emotional and cultural: accumulated insecurities, limiting beliefs, life experiences, and a lack of internal dialogue. The application of the Kaxan method facilitated processes of personal reinterpretation and the strengthening of emotional capital, enabling decision-making, risk acceptance, and the development of creative skills. Furthermore, it was shown that intercultural education legitimizes local productive practices and fosters the integration of cultural identity, community networks, and economic formalization. The findings indicate that conscious entrepreneurship is a viable path for promoting sustainable career trajectories by integrating the emotional, organizational, and sociocultural dimensions of the entrepreneur. Its potential to complement public employability policies and transform traditional job training models, especially in vulnerable communities, is highlighted. Finally, it is recommended that regulatory frameworks that recognize these dimensions and strengthen the inclusion of comprehensive approaches in economic and social development programs be further developed.